2013
DOI: 10.1007/s11746-013-2259-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pilot Plant‐Scale Ultrasound on Palm Oil Separation and Oil Quality

Abstract: The effects of ultrasonic standing waves on palm oil separation of ex-screw press feed from the mesocarp of the palm oil fruit, oil recovery and oil quality were determined. The ex-screw press feed at 85°C was pumped simultaneously into two identical vessels. One vessel was the control (non-ultrasound) and the other vessel (ultrasound) was fitted with two 400 kHz transducer plates operating at 13.4 kJ/kg, which were placed in direct contact with the feed. Oiling-off by gravity settling occurred at faster rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Thermodynamic parameters of the adsorption process, such as enthalpy (∆H 0 ), entropy (∆S 0 ) and Gibbs free energy (∆G 0 ) are important indicators for the practical application of U(VI) biosorption by microbes. The thermodynamic parameters can be calculated by the following equations [46]: (11) (12) ...where K d (=q e /C e ) is the distribution coefficient, ∆H 0 (kJ/mol), ∆S 0 (J/mol•K) and ∆G 0 (kJ/mol) are the enthalpy, entropy, and Gibbs free energy, respectively. The linear variation of lnK d versus 1/T is shown in Fig.…”
Section: Effect Of Temperature On Biosorption Of U(vi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamic parameters of the adsorption process, such as enthalpy (∆H 0 ), entropy (∆S 0 ) and Gibbs free energy (∆G 0 ) are important indicators for the practical application of U(VI) biosorption by microbes. The thermodynamic parameters can be calculated by the following equations [46]: (11) (12) ...where K d (=q e /C e ) is the distribution coefficient, ∆H 0 (kJ/mol), ∆S 0 (J/mol•K) and ∆G 0 (kJ/mol) are the enthalpy, entropy, and Gibbs free energy, respectively. The linear variation of lnK d versus 1/T is shown in Fig.…”
Section: Effect Of Temperature On Biosorption Of U(vi)mentioning
confidence: 99%
“…Uranium was classified as a confirmed human carcinogen by the Environmental Protection Agency (EPA) in 1996 [7][8]. Conventional methods of removing uranium pollutants, such as chemical precipitation, ion exchange, solvent extraction, evaporative recovery and membrane separation [9][10][11][12][13][14] consume large amounts of energy and can cause secondary pollution. They also have low removal efficiency when the ion concentration is less than 100 mg/L [15].…”
Section: Introductionmentioning
confidence: 99%
“…The deterioration of palm oil was determined by the DOBI method, as previously reported, [12] with a few modifications. About 0.2 g oil was weighed into 50 mL n-hexane (99%).…”
Section: Deterioration Of Bleachability Index (Dobi)mentioning
confidence: 99%
“…Tests demonstrated that tocols (tocotrienols, tocopherols) and other phytonutrients such as carotenoids, contributing to the orange-redish colour of the oil are not modified when subject to megasonic separation for about 60 min (Table 1) [15]. An enhanced rate of oil recovery due to megasonic processing can provide opportunities for decreasing traditional extraction temperatures below 90°C and therefore provide with crude palm oil of higher nutrient content.…”
Section: Palm Oilmentioning
confidence: 99%
“…Table 1: Quality parameters of palm oil separated from pressed oil palm fruit feeds after 400 kHz ultrasound processing. Data is compared with a commercial sample of palm oil using the conventional palm oil milling process taken on the same day in a palm oil mill (Adapted from Juliano et al [15]). …”
Section: Palm Oilmentioning
confidence: 99%